Nursing Process Training to Improve the Quality of Nursing Care Documentation - Harmini, Harmini; Supratman, Supratman; Yulian, Vinami (Interest : Jurnal Ilmu Kesehatan, 2024)
Background: The role of medical caretakers as well-being specialists incorporates a major commitment to well-being administrations in an effort to improve the quality of well-being administrations. A few variables that impact nursing documentation include the need for time, the need for vitality, the persistent stack, the need for information from medical caretakers around the documentation framework, the significance of reporting nursing care, and the need for support from nursing pioneers. The aim of this study is to analyze the effect of nursing process training on the quality of nursing care documentation. Methods: The research to be conducted uses a pre-experiment design research design with a one-group pre-post test-only model consisting of one intervention group. Data collection will be carried out from October to November 2023 in the inpatient room at the hospital. The population in this study was 486 nurses in Surakarat City. The sample was determined based on simple random sampling, so 82 nurses were selected. Results: The results of statistical tests explain that the value is -48.538 (t≠0). The t value can illustrate that there is a difference in the average score between the pre-test and post-test, where the average pre-test score (69.40) is smaller than the average post-test score (90.57) with a significant value ( p) = 0.000 (p<0.05). The pre-test score (69.40) is smaller than the average post-test score (90.57), with a significance value (p) = 0.000 (p<0.05). Conclusion: Nursing process training has been proven to be effective in influencing the documentation of the nursing process. It is recommended that health institutions provide ongoing training for nurses, not just as a one-time event.